An exploration of South Africa's innovation ecosystem for internet of things devices - Mokoka, Mmakgomo Didintle (My University, 2018)
An innovation ecosystem is a network of individuals and organisations with the aim of delivering a holistic product. The study aimed to understand South Africa’s Internet of Things innovation ecosystem. Internet of Things is defined as network-enabled objects which could communicate with one another. This growing trend was identified as an opportunity for South Africa to partake in the manufacturing thereof, provided that there was a well-functioning ecosystem in place. Through a review of existing literature, a framework was identified. A systematic literature review was conducted and it uncovered further elements to include in the framework. The study was exploratory in nature and made use of interviews as a method of data collection. Individuals involved in the manufacture of Internet of Things devices and individuals from institutions which supported such manufacturers were interviewed. The study aimed to understand how the actors within this ecosystem experienced Internet of Things innovation. Thematic content analysis was utilised to identify codes and themes in the data. The results of the study showed that several elements such as financing, infrastructure, regulations, ideas, knowledge networks, culture, interfaces, and architecture principles were in place, but some are not functional or work against entrepreneurs. Supporting institutions felt that they provided valuable services to manufacturing companies and that some of their challenges to providing these services stemmed from the manufacturers themselves. Manufacturing companies felt as though there were a few elements within the ecosystem which could be improved upon such as financing support, marketing support, regulations, skills, knowledge, knowledge networks, and knowledge sharing. The research created a platform for further studies to take place that investigate why South Africa’s Internet of Things innovation ecosystem is not functioning as well as those that are currently flourishing.
A research report submitted to the Faculty of Commerce, Law and Management, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce in Information Systems, Johannesburg 2018
Keywords: Internet of things; Embedded Internet devices